Research of additional materials on the basis of phosphorus-organic compounds - Ранський, А.П.; Диха, О.В.; Петрук, Р.В. (Problems of Tribology, 2014)
This paper presents a new way to get dialkildithio phosphates of zinc, which is additive to the lubricating compositions of different composition. Raw material for additives is off grade phosphorus content pesticide chemicals that by processing reagent method to dialkildithio phosphates recycled metals. Synthesized additives within lubricating compositions of different concentrations tested for durability using four-ball friction machine and gives positive results